(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
This study was conducted to investigate the effect of a previous history of exposure to contingency-shaped behavior or rule-governed behavior over the sensitivity to changing consequences of responding. A computerized procedure was used, independently of the presence of the researchers. A Matching-to-sample task procedure was programmed in computer with six male undergraduate, designated in two experimental conditions, organized in two different phases. In the Phase 1, three participants were training directly in contingency-shaped behavior procedure; the remains were designed to a rule-governed behavior procedure. In the Phase 2, all participants were exposed to conditions were discrepancies between rules and contingencies were designed. It was found that five of the six participants changed their responses when the contingencies were shifted. Sensitivity was showed independently of the previous history of learning. The effect of the computerized procedure over the results was discussed.